Euphemism analysis on the main character in Legally Blonde film - Ananta, Elsa Laura; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This research explores the use of euphemism in the film Legally Blonde, with a particular focus on Elle Woods as the main character. Euphemism is understood as a linguistic strategy used to avoid harsh, taboo, or impolite expressions, making communication more polite and socially acceptable. Through a qualitative descriptive approach, the research examines Elle’s utterances by applying Allan and Burridge’s (2006) euphemism framework and Palmer’s (1976) concept of meaning. The analysis identifies several types of euphemisms, including metaphor, circumlocution, understatement, omission, clipping, acronyms, borrowing, and hyperbole. The findings show that Elle uses euphemistic language not only to maintain politeness and navigate sensitive topics but also to challenge stereotypes and assert her identity in professional environments such as law school. Theoretically, this research contributes to sociolinguistic research by showing how euphemism functions as a form of language variation and politeness strategy. Practically, it provides useful insights for students, educators, and researchers in understanding euphemism in both literary works and real-life communication.